Cognitive function characteristics and influencing factors in patients with depressive disorders: a 5-year follow-up report based on the epidemiological survey of mental disorders in Shandong Province, China - Lin, Ziang; Wang, Qian; Li, Xiaojing; Wang, Can; Wang, Ruzhan; Wang, Chenghui; Ding, Hao; Qian, Liju; Wan, Xiaona; Tian, Xue; Hou, Zongyin; Liu, Fengjie; et al. (Frontiers in Psychiatry, 2024)
Objective: Cognitive impairment represents a notable feature of depressive disorders.Comprehending its characteristics and influencing factors is vital for patient rehabilitation.Methods: This study is based on the 2015 Shandong Province epidemiological survey of mental disorders, from which 871 individuals meeting DSM-IV criteria for depressive disorders were selected as the research group. Using 1:1:1 matching by sex, age, and residence, we randomly selected 825 individuals with no DSM-IV diagnosis but positive on GHQ-12 and additional risk assessments as the elevated risk control group, and 825 with negative screenings as the minimal risk control group. In 2020, a follow-up survey was conducted, resulting in a final analysis of 1,855 cases. The survey included demographic data, various clinical information, and a series of screening and questionnaire assessments.The current depressive group scored lower on the MoCA than the non-depressive group (t=8.86, P<0.01). The research group scored lower on the MoCA than the elevated and minimal risk group (F=11.98, P<0.01). The depression-unremitted group scored lower than the depression-remitted group (t=6.44, P<0.01). The Analysis indicated that males, with better life quality, poor early psychological statusand, and longer education were associated with higher MoCA scores. Conversely, older age, rural residency, employment, current depression, and poor marital were associated with lower MoCA scores.Individuals with depression commonly suffer cognitive impairment, which tends to partially improve as depression remits. Individual cognitive function is influenced by early psychological health, depressive status, quality of life, age, sex, educational level, residence, occupational, and marital status.